Identifying adverse childhood experiences and mental health needs among a small sample of pregnant women who use cannabis - Aubrey Jones; Lisa M. Blair; Julie A. Kurzer; Kathy Rademacher; Letitia Ducas; Cynthia Cockerham; Kristin Ashford (Frontiers in Psychiatry)
IntroductionAs the legalization of cannabis becomes more widespread use has steadily increased. Approximately 5 percent of pregnant individuals self-report use during pregnancy.MethodsThis study uses a mixed methods approach to examine adverse childhood experiences, mental health needs, and cannabis use among a small sample (N =59) of women. Cumulative ACE scores of four or more were considerably high within this sample compared to the US average.ResultsResults of a binary logistic regression indicate an association between ACEs and Cannabis use (OR 1.27, 95% CI (1.002- 1.616) when controlling for maternal age and anxiety. Qualitative results identified two main sub-themes: Medical Use for Mental Health Symptoms and Concerns about Negative Mental Health Effects Postpartum.DiscussionResults suggest a need for patient education about cannabis use in pregnancy and trauma informed care.